2009
DOI: 10.1038/nrn2786
|View full text |Cite
|
Sign up to set email alerts
|

Prion-like mechanisms in neurodegenerative diseases

Abstract: Many non-infectious neurodegenerative diseases are associated with the accumulation of fibrillar protein. These diseases all exhibit phenotypic diversity and propagation of pathology that is reminiscent of prionopathies. Furthermore, emerging studies of amyloid-β, α–synuclein, and tau proteins suggest that they share key biophysical and biochemical characteristics with prions. Propagation of protein misfolding in these diseases may therefore occur via mechanisms similar to those underlying prion pathogenesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
524
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 667 publications
(541 citation statements)
references
References 61 publications
13
524
1
3
Order By: Relevance
“…Moreover, recent studies have shown that propagation and seeding of Aβ, tau, and α-syn in a prion-like manner might also contribute to neurodegeneration [22][23][24][25][26][27][28]. Remarkably, there is also evidence that these various protein aggregates can interact with each other [29].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies have shown that propagation and seeding of Aβ, tau, and α-syn in a prion-like manner might also contribute to neurodegeneration [22][23][24][25][26][27][28]. Remarkably, there is also evidence that these various protein aggregates can interact with each other [29].…”
Section: Introductionmentioning
confidence: 99%
“…the prion protein or β-amyloid (Aβ) respectively, that are deleterious to neuronal function, as reviewed recently (Frost and Diamond, 2009). However, prionopathies are unique among neurodegenerative diseases because they are infectious.…”
Section: Micrornas and Prion Diseasementioning
confidence: 99%
“…The pathogenic isoform of the cellular PrP C , or a closely related molecule, is the causative agent of transmissible spongiform encephalopathies (TSE), that comprise a group of neurodegenerative diseases including bovine spongiform encephalopathy (BSE) in cattle, Scrapie in sheep, and Creutzfeldt-Jakob disease (CJD) in humans. Although recent studies have highlighted prion-like mechanisms of propagation of protein misfolding in other neurodegenerative diseases, such as AD (Frost and Diamond, 2009), the molecular mechanisms underlying prion-induced neurodegeneration, which coincides with neuronal loss and leads to death of the host, remains to be clearly defined.…”
Section: Micrornas and Prion Diseasementioning
confidence: 99%
“…This process can be replicated in vitro by subjecting prions to a cyclic process of fibril fragmentation and fibril growth, demonstrating that autocatalytic seeded aggregation is the molecular basis of prion replication [23,24]. Recent data indicate that prion-like replication can occur in many, if not all, amyloid diseases [25,26]. Inoculating young AD model mice with brain homogenate from late-stage disease mice accelerates their disease progression [27].…”
mentioning
confidence: 99%